Simulation as a Training Method for the Professionalization of Teams - Flentje, Markus; Eismann, Hendrik; Sieg, Lion; Friedrich, Lars; Breuer, Georg (AINS - Anästhesiologie. Intensivmedizin. Notfallmedizin. Schmerztherapie., 2018)
Simulation as an educational method can be applied to the training of processes, technical and non-technical skills. This article focuses on the role of simulation in crisis resource management and non-technical skills. A realistic work environment requires well-trained staff regarding simulation technology and communication. A training (unit) is divided into three sections. During the briefing the team is introduced to the scenario. Afterwards, the patient is treated by an interdisciplinary team. Communication under the pressure of action, even if one does not agree with the approach of the colleagues, should be practiced. After the scenario a structured debriefing is conducted. The trainer supervises the reflection of the teams' actions. Various methods such as "guided team self-correction", "advocacy-inquiry" and the "TeamGAINS"-approach are available for this decisive phase of the training. A safe environment is guaranteed, video recordings will never leave the training. Active experimentation, concrete experiences and accurate reflection are the key factors of success for the method simulation. Positive effects on critical incidents, resuscitation outcome and improvement of team climate can be observed after simulation training.
EVALuna2:213377